Sophorolipid Biosurfactant Can Control Cutaneous Dermatophytosis Caused by Trichophyton mentagrophytes - Sen, Suparna; Borah, Siddhartha Narayan; Kandimalla, Raghuram; Bora, Arijit; Deka, Suresh (Frontiers in Microbiology, 2020)
Trichophyton mentagrophytes, a zoophilic species, is one of the most frequently isolated dermatophytes in many parts of the world. This study investigated the efficacy of a sophorolipid (SL-YS3) produced by Rhodotorula babjevae YS3 against dermatophytosis caused by Trichophyton mentagrophytes. SL-YS3 was characterized by gas chromatography-mass spectrometry (GC-MS) and ultra-performance liquid chromatography coupled with electrospray mass spectrometry (UPLC-ESI-MS). SL-YS3 comprised of six different fatty acids as the hydrophobic components of constituent congeners and sophorose as the hydrophilic component. Inhibitory effects of purified SL-YS3 against hyphal growth was found to be 85% at 2 mg ml-1 concentration, and MIC was 1 mg ml-1. Microscopic examination with scanning electron microscopy (SEM), atomic force microscopy (AFM), and confocal laser scanning microscopy (CLSM) revealed that SL-YS3 exerts its effect by disrupting cell membrane integrity causing cell death. SL-YS3 was also effective in reducing the biofilms formed by T. mentagrophytes, which was observed spectrophotometrically with crystal-violet staining and further validated with SEM and CLSM studies of treated biofilms. In vivo studies in a mouse model of cutaneous dermatophytosis involving macroscopic observations, percent culture recovery from skin samples, and histopathological studies showed that SL-YS3 could effectively cure the infected mice after 21 days of topical treatment. Terbinafine (TRB) was used as a standard drug in the experiments. We demonstrate, for the first time, the antidermatophytic activity of a sophorolipid biosurfactant. The findings are suggestive that SL-YS3 can be formulated as a novel antifungal compound to treat cutaneous mycoses caused by T. mentagrophytes.